Overview of tuned liquid dampers and possible ways of oscillation damping properties improvement (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays liquid tuned dampers are used in high-rise buildings and many others “dynamically sensitive” engineering structures. Liquid damper properties can be widely changed using different shapes of water containers, additional barriers inside, different types of liquid etc. Different types of liquid dampers exist or are proposed by researchers. Main types of liquid dampers are observed and compared in the paper.One of the main disadvantages of the majority of liquid dampers is that only one main oscillation frequency is damped, that is not enough for the structures, where different vibrations modes are essential simultaneously. Existing solutions of this problem are examined in the paper.